Description of a quality improvement training programme for health professionals in the ministry of health and social services in Namibia - Nangombe, Julia Paul; Amukugo, Hans Justus (International Journal of Health, 2016)
The aim of this paper is to describe the quality improvement training programme for health professionals in the Ministry of Health and Social Services in Namibia. The Practice Oriented Theory of Dickoff (1968) was used as practical guidelines to develop the conceptual framework. This framework was employed during the research and the educational programme development process. During the research process, the agent was the researcher; recipients (Managers/leadership and health professionals); the context (MoHSS head office and healthcare facilities); dynamics (findings for objective one and two); Procedure (research process) and terminus (foundations for development of educational programme).Â For the educational programme developing process, agent (quality specialist), recipients (health professional), context (health facilities), procedure (training programme for health professionals), dynamics, (challenges hampering successful implementation of the programme) and the terminus (knowledge, skills and abilities acquired through the training programme). During the development of the quality improvement training programme, two main theories were adapted. The most prominent one was a model by Meyer and Van Niekerk (2008), which was adapted to guide the process of developing the training programme. Kolbâ€™s experiential learning theory was used to explain the learning process and styles of developing knowledge through experiences.The content of the training programme was derived from five main themes, 17 sub-themes and the conceptual framework based on the situation analysis about challenges faced by the health care facilities. The five themes were lack of implementation of policies and guidelines; inadequate resources; lack of interpersonal relationships; inadequate understanding of quality assurance and quality improvement; and inadequate research to provide evidence-based information during treatment and patient care.The educational programme consisted of the purpose / aim, objectives, structure / design, facilitation process, implementation process, and evaluation of the programme.